Tissue culture coupled with a gas exchange system offers new perspectives on phenotyping the developmental biology of Solanum lycopersicum L. cv. ‘MicroTom’ - Pepe, Marco; Marie, Telesphore R. J. G.; Leonardos, Evangelos D.; Hesami, Mohsen; Rana, Naheed; Jones, Andrew Maxwell Phineas; Grodzinski, Bernard (Frontiers in Plant Science, 2022)
Solanum lycopersicum L. cv. ‘Microtom’ (MicroTom) is a model organism with a relatively rapid life cycle, and wide library of genetic mutants available to study different aspects of plant development. Despite its small stature, conventional MicroTom research often requires expensive growth cabinets and expansive greenhouse space, limiting the number of experimental and control replications needed for significant experiments, and can render plants susceptible to pests and disease. Thus, alternative experimental approaches must be devised to reduce the footprint of experimental units and limit the occurrence problematic confounding variables. Here, tissue culture is presented as a powerful option for MicroTom research that can quell the complications associated with conventional MicroTom research methods. A previously established, non-invasive, analytical tissue culture system is used to compare in vitro and conventionally produced MicroTom by assessing photosynthesis, respiration, diurnal carbon gain, and fruit pigments. To our knowledge, this is the first publication that measures in vitro MicroTom fruit pigments and compares diurnal photosynthetic/ respiration responses to abiotic factors between in vitro and ex vitro MicroTom. Comparable trends would validate tissue culture as a new benchmark method in MicroTom research, as it is like Arabidopsis, allowing replicable, statistically valid, high throughput genotyping and selective phenotyping experiments. Combining the model plant MicroTom with advanced tissue culture methods makes it possible to study bonsai-style MicroTom responses to light, temperature, and atmospheric stimuli in the absence of confounding abiotic stress factors that would otherwise be unachievable using conventional methods.